Effect of Electroacupuncture at Neiguan (PC6) Combined With Zhigancao Decoction on Atrial Electromechanical Coupling and Inflammatory Cytokines in Patients With HFpEF and Atrial Fibrillation - Beibei Shi; Jinyi Jiang (Acupuncture & Electro-Therapeutics Research: International Journal of Integrated Medicine, 2026)
Objective This article aims to investigate the effect of electroacupuncture (EA) at Neiguan (PC6) combined with Zhigancao decoction on atrial electromechanical coupling and serum inflammatory cytokines in patients with heart failure with preserved ejection fraction (HFpEF) and atrial fibrillation (AF). Methods This retrospective analysis included 103 patients with HFpEF and AF. All patients received conventional Western medical therapy; 48 patients (Chinese medicine group) were additionally given oral Zhigancao decoction, and 55 patients (combination group) received EA at PC6 on this basis, with a treatment course of 8 weeks. Inflammatory cytokine levels, atrial electromechanical coupling parameters, echocardiographic indices, European Heart Rhythm Association (EHRA) symptom classification, and adverse events were compared between the two groups before and after treatment. Results After 8 weeks of treatment, serum high-sensitivity C-reactive protein, interleukin-6, and tumor necrosis factor-alpha levels, interatrial/atrioventricular electromechanical delay, E / e ′ ratio, and AF episode frequency decreased, while left atrial reservoir/contractile strain and left ventricular ejection fraction increased in both groups. The combination group showed more favorable posttreatment values than the Chinese medicine group (all P < 0.05). The posttreatment EHRA symptom-class distribution was more favorable in the combination group than in the Chinese medicine group ( P < 0.05). Conclusion EA at PC6 combined with Zhigancao decoction was associated with lower inflammatory marker levels, improved atrial electromechanical coupling parameters, better cardiac functional indices, and symptom relief in patients with HFpEF and AF. Due to the retrospective nonrandomized study design, these findings should be interpreted as associations rather than causal treatment effects.